ORO DENTAL HEALTH: AWARENESS AND PRACTICES - Nagina Parveen; Bilal Ahmed (Journal of University Medical & Dental College, 1970)
ABSTRACT Objective: To assess the knowledge, attitude, practices and perceptions regarding oro-dental health in the patients attending the outpatient department of Nishtar Institute of Dentistry, Multan, Pakistan. Methodology: This was a cross sectional descriptive hospital based survey, conducted in Nishtar Institute of Dentistry, Multan, Pakistan from January 2010 to March 2010. A total of 221 subjects were interviewed on a questionnaire proforma using Non Probability convenient sampling technique. SPSS version 17.0 was used to analyze the collected data. Results: Of the study participants, 41.7%, received information regarding oral health mainly from media and 46.2% from Community members. 64.3% of the study participants (Male 55.6% & Female 44.4%) knew the reason that eating sugars causes tooth decay and 47.1% were afraid of dental check up because of pain perception. Results showed that 46.2% (Male 51.9%: Female: 48.1%) brushed their teeth once a day and 6.9% did not brushed at all. It was found that 42.5% (Male: 46.8%; Female: 53.2%) of study participants visited the dentist during the last 6 months and about 56.1% of the subjects came because of dental pain. Conclusion: Results of this study suggest that oral health KAP among study participants was poor and needs to be improved. Findings of this study also show that utilization of available dental service is mainly for emergency pain relief & very occasionally for routine oral health maintenance. Based upon these findings, systematic community-oriented oral health promotion programs are needed to target the lifestyles in different general population groups.